INFLUENCE OF SPECIALIZATION, SIZE AND TENURE OF AUDIT FIRM ON EARNING MANAGEMENT OF MANUFACTURING COMPANIES LISTED ON BEI DURING 2014-2016 - Praananta O.W. (Russian Journal of Agricultural and Socio-Economic Sciences, 2019)
This research was conducted to determine the effect of audit quality tested with three variables, namely Audit Firm Specialization, Audit Firm Size, and Audit Firm Tenure on earning management. The population taken in this study was manufacturing companies listed on the Indonesia Stock Exchange for the 2014-2016, and samples taken based on several criteria, namely: (a) listed companies during the observation period, (b) companies not IPO during the observation period, (c) the company is not delisted in the observation period, etc. From these criteria, 202 sample companies will be tested using the SPSS technique. The results obtained from this study were (1) Audit Firm Specialization influence on earning management was rejected (2) Audit Firm size had an influence earning management was rejected, and (3) Audit Firm tenure had an influence on earning management was rejected.